Influence of Branding on Consumer Behavior: Case of Manhattan Hotel, Kabale Municipality Kigongi. - Mugisha, Ian (Kabale University, 2023)
This study investigated the role of branding on consumer behavior, and how it can influence them on how they can access the hotel for services. The aim of the study was to investigate how branding can provide value and how it can influence guest's to pick a hotel. Those objectives of this research were to analyze the influence of branding on consumer behavior, hence answering the researcher's questions. Manhattan Hotel Kabale served as the case study for this thesis. The concepts of branding, and the respective travel motivation have been researched by the researcher; as well as the luxury hospitality hotel company, and the example. of the hotel group Manhattan Hotel Kabale. In order to produce a balanced outcome, the researcher decided to address the matter from both sides: supply and demand. An in---depth interview with the Manager of the Manhattan Hotel Kabale, was carried out and served as the supply side (hotel company) representation; while a survey with the respective hotel's guests served as the demand side representation. The study found that the concept of branding allows a company to standout in its marketplace. Furthermore, according to the 51 guests who completed the survey, the study found that the important characteristics when choosing a hotel are location, followed by hotel facilities and level of service. Concerning guest loyalty, the supply side (hotel) believes that loyal guests are created via exceptional service. Findings from the survey showed that the hotel guests' ( demand side) loyalty was a ranging between committed and non---committed guests. Regarding how a brand provides value, Manhattan Hotel Kabale ensures quality via the Manhattan DNA: five values set by the hotel company to incorporate with service delivery throughout all guest touch points. In addition, the hotel conducts internal and external checks to guarantee service quality. Manhattan's values and the checks conducted by the hotel were found to be effective, as the survey showed that a remarkable percentage of the sample of guests would spread positive word---of---mouth about their respective stay. The findings of the paper are vital, as they explain the significance of branding on the respective travel motivation.